A Note on the Ratio of Two Normally Distributed Variables - Hayya, Jack; Armstrong, Donald; Gressis, Nicolas (Management Science, 1975)
This note is a continuation of a previous paper on normal approximations of standard forms. The standard form treated here is the ratio of two normally distributed variables. It is found that a suitable transformation of this ratio is approximately normally distributed provided that the coefficient of variation of the denominator is less than 0.39.